Differences

This shows you the differences between two versions of the page.

Link to this comparison view

Both sides previous revision Previous revision
physics_chemistry:point_groups:d3d:orientation_zx_b [2018/09/06 13:08]
Maurits W. Haverkort
physics_chemistry:point_groups:d3d:orientation_zx_b [2018/09/06 13:36] (current)
Maurits W. Haverkort
Line 505: Line 505:
  
  ​$$A_{k,​m} = \begin{cases}  ​$$A_{k,​m} = \begin{cases}
- ​\frac{1}{5} (\text{Ea1g}+2 (\text{Eeg$\pi $}+\text{Eeg$\sigma ​$})) & k=0\land m=0 \\ + ​\frac{1}{5} (\text{Ea1g}+2 (\text{Eeg}\pi +\text{Eeg}\sigma )) & k=0\land m=0 \\ 
- ​\text{Ea1g}-\text{Eeg$\pi $}-2 \sqrt{2} \text{Meg} & k=2\land m=0 \\ + ​\text{Ea1g}-\text{Eeg}\pi -2 \sqrt{2} \text{Meg} & k=2\land m=0 \\ 
- i \sqrt{\frac{7}{5}} \left(-\sqrt{2} \text{Eeg$\pi $}+\sqrt{2} \text{Eeg$\sigma ​$}+\text{Meg}\right) & k=4\land (m=-3\lor m=3) \\ + i \sqrt{\frac{7}{5}} \left(-\sqrt{2} \text{Eeg}\pi +\sqrt{2} \text{Eeg}\sigma +\text{Meg}\right) & k=4\land (m=-3\lor m=3) \\ 
- ​\frac{1}{5} \left(9 \text{Ea1g}-2 \text{Eeg$\pi $}-7 \text{Eeg$\sigma ​$}+10 \sqrt{2} \text{Meg}\right) & k=4\land m=0+ ​\frac{1}{5} \left(9 \text{Ea1g}-2 \text{Eeg}\pi -7 \text{Eeg}\sigma +10 \sqrt{2} \text{Meg}\right) & k=4\land m=0
 \end{cases}$$ \end{cases}$$
  
Line 532: Line 532:
 <code Quanty Akm_D3d_Zx_B.Quanty>​ <code Quanty Akm_D3d_Zx_B.Quanty>​
  
-Akm = {{0, 0, (1/5)*(Ea1g + (2)*(Eeg\[Pi] ​Eeg\[Sigma]))} ,  +Akm = {{0, 0, (1/5)*(Ea1g + (2)*(EegPi EegSigma))} ,  
-       {2, 0, Ea1g + (-1)*(Eeg\[Pi]) + (-2)*((sqrt(2))*(Meg))} ,  +       {2, 0, Ea1g + (-1)*(EegPi) + (-2)*((sqrt(2))*(Meg))} ,  
-       {4, 0, (1/​5)*((9)*(Ea1g) + (-2)*(Eeg\[Pi]) + (-7)*(Eeg\[Sigma]) + (10)*((sqrt(2))*(Meg)))} ,  +       {4, 0, (1/​5)*((9)*(Ea1g) + (-2)*(EegPi) + (-7)*(EegSigma) + (10)*((sqrt(2))*(Meg)))} ,  
-       ​{4,​-3,​ (I)*((sqrt(7/​5))*((-1)*((sqrt(2))*(Eeg\[Pi])) + (sqrt(2))*(Eeg\[Sigma]) + Meg))} ,  +       ​{4,​-3,​ (I)*((sqrt(7/​5))*((-1)*((sqrt(2))*(EegPi)) + (sqrt(2))*(EegSigma) + Meg))} ,  
-       {4, 3, (I)*((sqrt(7/​5))*((-1)*((sqrt(2))*(Eeg\[Pi])) + (sqrt(2))*(Eeg\[Sigma]) + Meg))} }+       {4, 3, (I)*((sqrt(7/​5))*((-1)*((sqrt(2))*(EegPi)) + (sqrt(2))*(EegSigma) + Meg))} }
  
 </​code>​ </​code>​
Print/export